Numerical analysis of recycled aggregate concrete-filled steel tube stub columns. Issue 5 (May 2016) - Xiang, Xingyun; Cai, CS; Zhao, Renda; Peng, Hui
This article presents a numerical analysis on the behavior of square recycled aggregate concrete-filled steel tube stub columns with the cold-formed hollow structural steel tube being used. A nonlinear finite element model for the square recycled aggregate concrete-filled steel tube stub column under axial compression has been developed using the general-purpose finite element program. An equivalent stress-strain model is proposed to simulate the behavior of the recycled aggregate concrete confined by a steel tube. The results obtained from the finite element model are compared with the experimental data. The comparison indicates that the finite element model is capable of predicting the mechanical behavior of the square recycled aggregate concrete-filled steel tube stub columns. After the validation of the numerical model, the effects of the recycled aggregate replacement ratio on the behavior of the square recycled aggregate concrete-filled steel tube stub columns are investigated. Furthermore, the applicability of the current design specifications and the proposed empirical formulas by various researchers to predict the ultimate compressive strengths of the recycled aggregate concrete-filled steel tube stub columns are examined. The comparative study shows that the specification Eurocode 4 gives closer prediction of the ultimate compressive strength than the other methods.